Biosorption of Arsenic(III) from Aqueous Solutions by Modified Fungal Biomass of Paecilomyces sp. (22nd October 2013) - Acosta Rodríguez, Ismael; Martínez-Juárez, Víctor M.; Cárdenas-González, Juan F.; Moctezuma-Zárate, María de Guadalupe
Abstract : The biosorption of As(III) on iron-coated fungal biomass of Paecilomyces sp. was studied in this work. It was found that the biomass was very efficient removing the metal in solution, using Atomic Absorption, reaching the next percentage of removals: 64.5%. The highest adsorption was obtained at pH 6.0, at 30°C after 24 hours of incubation, with 1 mg/L of modified fungal biomass.